Delayed resistance to transgenic cotton in pink bollworm - Tabashnik, Bruce E. (National Academy of Sciences, 2005)
Transgenic crops producing Bacillus thuringiensis (Bt) toxins kill some key insect pests and thus can reduce reliance on insecticides. Widespread planting of such Bt crops increased concerns that their usefulness would be cut short by rapid evolution of resistance to Bt toxins by pests. Pink bollworm (Pectinophora gossypiella) is a major pest that has experienced intense selection for resistance to Bt cotton in Arizona since 1997. We monitored pink bollworm resistance to Bt toxin for 8 years with laboratory bioassays of strains derived annually from 10-17 cotton fields statewide. Bioassay results show no net increase from 1997 to 2004 in the mean frequency of pink bollworm resistance to Bt toxin. A synthesis of experimental and modeling results suggests that this delay in resistance can be explained by refuges of cotton without Bt toxin, recessive inheritance of resistance, incomplete resistance, and fitness costs associated with resistance.